Effect of experimental treatment on housekeeping gene expression: validation by real-time, quantitative RT-PCR - Schmittgen, T.D.; Zakrajsek, B.A.
The effects of serum on the expression of four commonly used housekeeping genes were examined in serum-stimulated fibroblasts in order to validate the internal control genes for a quantitative RT-PCR assay. NIH 3T3 fibroblasts transfected with an inducible chimeric gene were serum-starved for 24 h and then induced with 15 percent serum for 8 h. Serum did not alter the amount of total RNA that was expressed in the cells, however, the amount of mRNA significantly increased over time with serum-stimulation. Both messenger and total RNA from each of the time points were reverse transcribed under two different conditions; one in which the reactions were normalized to contain equal amounts of RNA and another series of reactions that were not normalized to RNA content. The resulting cDNA was amplified by real-time, quantitative PCR using gene-specific primers for b-actin, b-2 microglobulin, glyceraldehyde-3-phosphate dehydrogenase (GAPDH)and 18S ribosomal RNA. The expression of b-actin and GAPDH increased up to nine- and three-fold, respectively, under all conditions of reverse transcription (P,0.01). The expression of 18S rRNA increased with serum-stimulation when the cDNA synthesized from non-normalized, total RNA was assayed (P,0.01)but not when the reverse transcriptions were normalized to RNA content (P.0.05). The expression of b-2 microglobulin increased up to two-fold when assayed from cDNA synthesized from non-normalized mRNA, but was unaffected by serum when the reverse transcriptions were normalized to mRNA. b-2 Microglobulin non-normalized reverse transcription reactions. Thus, b-2 microglobulin and 18S rRNA are suitable internal control genes in quantitative serum-stimulation studies, while b-actin and GAPDH are not. The internal control gene needs to be properly validated when designing quantitative gene expression studies.
Keywords: REAL-TIME PCR; QUANTITATIVE RT-PCR; GENE EXPRESSION; SYBR GREEN; SERUM-STIMULATION